2018
DOI: 10.21859/ijnr-12065
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Self-compassion, Social Support and Hope with Subjective Well-being of Nursing Students

Abstract: Introduction: Subjective well-being is one of the important components of mental health, identification of effective factors of which is important, such as self-compassion, social support and hope. This research aimed at investigating the relationship of self-compassion, social support and hope with subjective well-being of nursing students. Methods: The present research was a descriptive-analytical correlation study. The population included all nursing students of Islamic Azad University of Ahvaz branch durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…The findings of this study are in line with the results of Todoro, Sherman, and Kilby [33], Fong and Kai [34], Yang et al [35], Akin and Akin [23], Zarei and Fooladvand [19], and Dashtbozorgi and Homayi's [18] studies. No inconsistent study was found in previous studies.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The findings of this study are in line with the results of Todoro, Sherman, and Kilby [33], Fong and Kai [34], Yang et al [35], Akin and Akin [23], Zarei and Fooladvand [19], and Dashtbozorgi and Homayi's [18] studies. No inconsistent study was found in previous studies.…”
Section: Discussionsupporting
confidence: 91%
“…Self-compassion is also one of the ways to adapt to stressful life situations and can also reduce cognitions focused on negative points by reducing negative reactions; thereby, it improves individuals' performance and well-being [37]. Dashtbozorgi and Homayi [18], in their research, concluded that individuals with high selfcompassion treat themselves with kindness, concern, and affection when they experience negative events, leading to increased social communication and reduced self-criticism, rumination, and suppression of negative thoughts, and ultimately to psychological well-being and hope for a better future. Hope causes individuals who have failed in their lives or suffer from physical and mental problems to return to their healthy and happy lives through reconstructing their damaged emotions and feelings and strengthens their life satisfaction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation